Improving the Design of the Multi-Pocket Stone Trapper (Texas Journal of Engineering and Technology, 2022)
In order to increase the efficiency of the device for retaining heavy impurities in the cotton gins during the transportation of cotton by air, the design of the separator has been improved, as a result of which high efficiency is achieved in the separation of heavy impurities in the pneumatic transport device.